A Bibliometric Citation Analysis on Green Marketing and Waste Management - Omar Zaki, Hafizah; Rosli, Nadzirah (Universiti Utara Malaysia Press, 2024)
The research interest in the field of green marketing and waste management can be demonstrated through the published literature on the topic. However, there is a paucity of extensive and systematic research focusing on the evolution of this discipline in terms of its citation work. The main objective of this study is to explore the status of scholarly works on green marketing and waste management through a bibliometric citation and networking analysis of papers published from 2012 to 2021. The data was extracted from the Web of Science (WOS) utilizing the Preferred Reporting Items for Systematic Review and Meta-Analysed (PRISMA) review process. The VOSviewer software was used to visualize the networking linkages. The findings of descriptive analysis showed that publications and citations related to green marketing and waste management are highest in 2021. Likewise, the networking analysis showed that the Science of the Total Environment journal has the highest citation counts, while Wan Yinfeng, Wang Junshi, Xu Guoping and Yi Huang are the authors with the highest citation counts, respectively. The findings also uncovered Sinosteel Wuhan Safety & Environmental Protection Research Institute (WSEPRI) as the most cited institution. Co-authorship and co-occurrence analysis were also found to provide significant discoveries. This study offers future scholars’ knowledge on the analysis of cited journals, papers, authors, institutions, and countries in the same field. Overall, the study serves as a guide for journal editorial boards on the growth among authors and networking opportunities in the field of green marketing and waste management, especially at the international level.